Budaya Populer dalam Praktik Konversi Modal di Arena Pembelajaran Bahasa Jepang - Wury Dwiwardani; Oki Rahadianto Sutopo; Wiwik Sushartami (Vocational College of Diponegoro University, 2026)
Various popular Japanese culture products available online are widely believed to support the acquisition of Japanese language proficiency. However, this potential is not always equally realized in learning practices. This study aims to analyse how the process of capital conversion occurs among students who are fans of Japanese popular culture in the arena of Japanese language learning in higher education. The research was conducted using qualitative research methods, with a narrative research approach, within the framework of Bourdieu’s theory, particularly as it relates to fields, capital, and habitus. The research informants were four students from the Japanese language studies program. The results of the research indicate that interaction with Japanese popular culture can accumulate valuable Japanese language skills in the Japanese language learning arena, but this process does not occur automatically. The success of conversion depends on the interaction between habitus, the configuration of initial capital, and reflexivity, through which students adjust their practices in response to the dominant rules and dynamics of the field.